2008
DOI: 10.1107/s1600536807068821
|View full text |Cite
|
Sign up to set email alerts
|

2-Methyl-N-phenylbenzamide

Abstract: In the structure of the title compound (NP2MBA), C14H13NO, the conformation of the C—O bond is syn to the ortho-methyl substituent in the benzoyl phenyl ring, while the N—H bond is anti to the ortho-methyl substituent. The structure of NP2MBA closely resembles that of 2-chloro-N-phenyl­benzamide, with similar bond parameters. The dihedral angle between the phenyl and benzoyl rings is 88.05 (5)°. Mol­ecules are linked into a chain through N—H⋯O hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 5 publications
5
18
0
Order By: Relevance
“…In structural chemistry, a multitude of crystal structure studies have been reported to date on a variety of organic molecular classes and with a particular emphasis on polymorphism, pseudopolymorphism and isomers (Gelbrich et al, 2007;Wardell et al, 2007Wardell et al, , 2008Chopra & Row, 2008). The variety and sizes of structural series reported are expanding rapidly and notable examples include benzoate esters (Gowda, Foro, Sowmya & Fuess, 2008) and both mono/dimethyl-and chlorobenzamides (Gowda, Foro, Babitha & Fuess, 2008). Series such as these provide a 'goldmine' of structural data for ongoing data analyses.…”
Section: Commentmentioning
confidence: 99%
“…In structural chemistry, a multitude of crystal structure studies have been reported to date on a variety of organic molecular classes and with a particular emphasis on polymorphism, pseudopolymorphism and isomers (Gelbrich et al, 2007;Wardell et al, 2007Wardell et al, , 2008Chopra & Row, 2008). The variety and sizes of structural series reported are expanding rapidly and notable examples include benzoate esters (Gowda, Foro, Sowmya & Fuess, 2008) and both mono/dimethyl-and chlorobenzamides (Gowda, Foro, Babitha & Fuess, 2008). Series such as these provide a 'goldmine' of structural data for ongoing data analyses.…”
Section: Commentmentioning
confidence: 99%
“…We assume that realistic conformations explaining the crystallographic data will be within a limited RMSD distance of the published PDB structure; this follows similar assumptions in previous work [7,10]. However, hinge motion, if present in a single crystal specimen, can also be detected by sampling in a larger conformational space around the PDB structure.…”
Section: Methodsmentioning
confidence: 87%
“…Multi-conformer approaches have long been the norm when modeling NMR data. It has been suggested that, for an accurate representation of the physical heterogeneity in a protein, such multiple-conformer models also be used to explain X-ray crystallography data [8-10]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations